Corporate Environmental Disclosure and Earnings Quality: Evidence from Malaysian Firms - Syed Ullah (Arthatama: Journal of Business Management and Accounting, 2018)
This research investigates the relationship between corporate environmental disclosure and earnings management. This research used the sample data of 134 companies listed on the stock exchange of Bursa Malaysia from 2013 to 2019. However, three different theoretical frameworks were used in this study, namely: signaling theory, agency theory and stakeholders’ legitimacy, with the aim of identifying the relationship between environmental disclosure and earnings management. Therefore, this research did not find any statistically significant relationship between environmental disclosure and earnings management which was measured by various methods, using discretionary accruals. Lastly, this research also found that the attributes of corporate governance can influence the relationship between environmental disclosure and earnings management.